1978
DOI: 10.1111/j.1365-2427.1978.tb01473.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and growth of Asellus aquaticus (Isopoda) on food items from the littoral of Windermere, including green leaves of Elodea canadensis

Abstract: In the laboratory, Asellus aquaticus .devoured intact green leaves from growing shoots of the aquatic macrophyte Elodea canadensis. in four collections of A. aquaticus on Elodea in a lake (Windermere), c. 20% of the specimens contained in their guts fragments of green Elodea leaves; this material and pieces of oak (Quercus) were identified from characteristic leaf hairs. Some specimens had also eaten the filamentous alga Oedogonium. Fluorescence microscopy is a useful aid for screening Invertebrates that may h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 29 publications
3
51
0
1
Order By: Relevance
“…The extremely low elimination rate constants for pyrene and benzo[ghi]perylene in the peripheral compartment signify that some PAHs are strongly bound in stable compartments and probably will never leave the organism during its normal life span. In feeding experiments relative growth rates of 0.01-0.05 day -1 have been determined for freshwater isopods (45). It may be expected that growth dilution is an important factor leading to a reduced apparent bioconcentration of slowly exchanging compounds in the field situation.…”
Section: Resultsmentioning
confidence: 99%
“…The extremely low elimination rate constants for pyrene and benzo[ghi]perylene in the peripheral compartment signify that some PAHs are strongly bound in stable compartments and probably will never leave the organism during its normal life span. In feeding experiments relative growth rates of 0.01-0.05 day -1 have been determined for freshwater isopods (45). It may be expected that growth dilution is an important factor leading to a reduced apparent bioconcentration of slowly exchanging compounds in the field situation.…”
Section: Resultsmentioning
confidence: 99%
“…In toxicokinetic experiments with PAHs in A. aquaticus elimination rate constants decreased with increasing K ow (Van Hattum and Cid Montañés 1998). Using relative growth rate values for freshwater isopods (0.01-0.05 day Ϫ1 ) reported by Marcus et al (1978), it can be demonstrated that growth dilution is likely to restrain the maximum apparent bioconcentration. This may have been the case for compounds with elimination rate constants less than 0.01-0.05 day Ϫ1 , which were observed for PAHs with 5 Ͻ log K ow Ͻ 6.…”
Section: Biological Factorsmentioning
confidence: 99%
“…The suitability of the benthic invertebrate Asellus aquaticus (L.) as a model species for the monitoring of the bioavailability of sediment-bound trace metals has been previously demonstrated (Van Hattum et al 1991. Freshwater isopods are widely distributed in littoral habitats of many meso-and eutrophic waters in the northern hemisphere and usually represent an important food source for predatory invertebrates, fish, and waterfowl (Williams 1962;Marcus et al 1978). Previous work of our group on the bioconcentration and toxicokinetics of chlorpyrifos (Cid Montañés et al 1995) and PAHs (Cid Montañés 1994;Van Hattum and Cid Montañés 1998) indicated an absent biotransformation activity in A. aquaticus (L.).…”
mentioning
confidence: 99%
“…Asellus aquaticus has a one year life-cycle with increased growth rate at higher temperatures (Okland, 1978) and sexual maturity reached within 60 days at a temperature of 15 o C (Marcus et al 1978). A further 150-200 days is required for production of the next generation and each female produces 1-2 broods and the number of eggs produced can range from 21-100 as female length increases (Steel, 1961).…”
Section: Ecology Of Asellus Aquaticusmentioning
confidence: 99%
“…Asellus aquaticus has been suggested as a suitable species for use in sediment toxicity tests, since it is in continuous contact with the sediment and feeds on detritus (Marcus et al 1978).…”
Section: Sediment Requirementsmentioning
confidence: 99%